RAND Suicide Prevention Program Evaluation Toolkit - Acosta, Joie D.; Ramchand, Rajeev; Becker, Amariah; Felton, Alexandria; Kofner, Aaron (RAND Corporation, 2023)
Evaluating suicide prevention programs can be challenging because suicide is a rare event and prevention programs are often complex and multifaceted. The RAND Suicide Prevention Program Evaluation Toolkit uses checklists, worksheets, and templates to help program staff design an evaluation that is appropriate for their program type, available resources, and expertise and offers guidance on analyzing the resulting data to inform improvements.